2008
DOI: 10.1016/j.cellbi.2007.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdastrellic acid‐A inhibited PI3K/Akt pathway and induced apoptosis in human leukemia HL‐60 cells

Abstract: Increasing evidence suggests that aberrant activation of PI3K/Akt is involved in many human cancers, and that inhibition of the PI3K/Akt pathway might be a promising strategy for cancer treatment. Our investigation indicates that Rhabdastrellic acid-A, an isomalabaricane triterpenoid isolated from the sponge, Rhabdastrella globostellata, inhibits proliferation of HL-60 cells with an IC(50) value of 0.68mug/ml, and induces apoptosis. Rhabdastrellic acid-A also induces cleavage of the death substrate poly (ADP-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Other isomalabaricane triterpenoids were found to induce reactive oxygen species (ROS), decrease mitochondrial membrane potential, increase the levels of Bax and cytochrome c, decrease the levels of Bcl-2 and mediate a caspases-3 apoptotic pathway, but the molecular mechanisms responsible for triterpenoids-induced cell death have not been elucidated yet[5]. Also, our investigation showed that Rhabdastrellic acid-A induced apoptosis in HL-60 cells [4], but the development of apoptotic features in Hep3B and A549 cells following exposure to Rhabdastrellic acid-A was not observed.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Other isomalabaricane triterpenoids were found to induce reactive oxygen species (ROS), decrease mitochondrial membrane potential, increase the levels of Bax and cytochrome c, decrease the levels of Bcl-2 and mediate a caspases-3 apoptotic pathway, but the molecular mechanisms responsible for triterpenoids-induced cell death have not been elucidated yet[5]. Also, our investigation showed that Rhabdastrellic acid-A induced apoptosis in HL-60 cells [4], but the development of apoptotic features in Hep3B and A549 cells following exposure to Rhabdastrellic acid-A was not observed.…”
Section: Introductionmentioning
confidence: 79%
“…1), an isomalabaricane triterpenoid, was isolated from the yellow sponge Rhabdastrella globostellata (Carter) collected from the South China Sea near Hainan Island, People's Republic of China. Its structure was established on the basis of UV, IR, MS, 1 H-NMR, 13 C-NMR, and 2D NMR spectrometry [3], [4]. The relative and absolute stereochemistries were solved by NOESY and CD studies, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…together with stelletins E ( 60 ) and F ( 61 ) [78]. The E isomer of stelletin G ( 62 ) was isolated from the marine sponge Rhabdastrella globostellata collected from the South China Sea and it was given the trivial name rhabdastrellic acid–A ( 63 ) [75,76]. …”
Section: Triterpenes (C30)mentioning
confidence: 99%
“…Stelletins L ( 70 ) and M ( 71 ) exhibited selective cytotoxicity against stomach cancer AGS cells with IC 50 values of 3.9 and 2.1 μM, respectively [85]. Rhabdastrellic acid–A ( 63 ) also inhibited proliferation of human leukemia HL-60 cells with an IC 50 value of 1.5 μM through inhibition of the PI3K/Akt pathway and induction of caspase-3 dependent-apoptosis [76]. Only rhabdastrellin A ( 64 ) possessed moderate inhibitory activity toward human leukemia HL-60 cells (IC 50 = 8.7 μM) while other rhabdastrellins were inactive (IC 50 > 20 μM) [86].…”
Section: Triterpenes (C30)mentioning
confidence: 99%
“…Conversely, induction of a Th1 response may lead to protection against successful parasite establishment. This can be achieved by vaccination with appropriate parasite antigens using specific immunization routes (Al-Qaoud et al , 2008; Ding et al , 2008). Recently, DNA vaccination to viruses, bacteria and parasites has been used as a tool to study the effects of the immunization route (parenteral, intranasal, oral, intralymphatic and intrahepatic) on the immune response (Fynan et al , 1993; Chen, 1998; Sasaki et al , 1998; Maloy et al , 2001; Cruz-Revilla et al , 2006).…”
mentioning
confidence: 99%